(untitled) (Journal of the College of Basic Education, 2022)
The research aims to prepare rehabilitative exercises using water yoga in improving the range of motion and muscle strength of those with partial tears of the lateral ligament of the knee joint for soccer players. And to know the effect of rehabilitative exercises using water yoga in improving the range of motion of football players with partial tearing of the lateral ligament of the knee joint. The researcher used the experimental method in the (one group) method with two pre and posttests, due to its relevance to the nature of the problem. On a sample of football players with a partial tear of the lateral ligament of the knee joint (5). The injury was examined and diagnosed by the specialist physician (Dr. Muhammad Abdel Hajim) and it was proved that all the injuries are of the type (simple - medium) severity, then the tests were applied to measure the range of motion of the knee joint and after applying the approach for 12 weeks, the researcher used the statistical bag (SPSS) , To process the data obtained. In light of the findings of the researcher, he came out with the following conclusions: - The use of water yoga exercises has a positive effect in rehabilitating the partial tear of the lateral ligament of football players. Water yoga exercises have a positive effect on the range of motion (negative and positive) of the affected knee joint with a partial tear of the lateral ligament. The application of water yoga exercises to people with partial tear of the lateral ligament did not leave any negative effects on them, but rather they got positive changes and rapid improvement.